Benefits of a female coach mentorship programme on women coaches` development: an ecological perspective - Banwell, J.; Kerr, G.; Stirling, A. (Sports Coaching Review, 2021)
The development of women coaches is complex and dependent upon influences at individual, interpersonal, organisational, and sociocultural levels, as outlined by the Ecological-Intersectional Model (EIM). Mentorship is a notable strategy for supporting the development and advancement of women coaches, yet we know little about the benefits of mentorship for women coaches at each of these levels. The purpose of this study was to gain an ecological understanding of the benefits of mentorship for advancing women in coaching. More specifically, this study sought to explore the benefits of a Female Coach Mentorship Program on the various levels of the EIM model. In-depth, semi-structured interviews were conducted with seven women mentee coaches and a qualitative thematic analysis of the data revealed benefits of mentorship at the individual and interpersonal levels but not at the organisational and sociocultural levels. Recommendations are made to advance mentorship with further attention on the macro-levels of sport.